Neural Mechanisms Underlying Time Perception and Reward Anticipation - Apaydın, Nihal; Üstün, Sertaç; Kale, Emre H.; Çelikağ, İpek; Özgüven, Halise D.; Baskak, Bora; Çiçek, Metehan (Frontiers in Human Neuroscience, 2018)
Findings suggest that the physiological mechanisms involved in the reward anticipation and time perception partially overlap. But the systematic investigation of a potential interaction between time and reward systems using neuroimaging is lacking. Eighteen healthy volunteers (all right-handed) participated in an event-related functional magnetic resonance imaging (fMRI) experiment that employs a visual paradigm that consists monetary reward to assess whether the functional neural representations of time perception and reward prospection are shared or distinct. Subjects performed a time perception task in which observers had to extrapolate the velocity of an occluded moving object in “reward” vs. “no-reward” sessions during fMRI scanning. There were also “control condition” trials in which participants judged about the color tone change of the stimuli. Time perception showed a fronto-parietal (more extensive in the right) cingulate and peristriate cortical as well as cerebellar activity. On the other hand, reward anticipation activated anterior insular cortex, nucleus accumbens, caudate nucleus, thalamus, cerebellum, postcentral gyrus and peristriate cortex. Interaction between the time perception and the reward prospect showed dorsolateral, orbitofrontal, medial prefrontal and caudate nucleus activity. Our findings suggest that a prefrontal-striatal circuit might integrate reward and timing systems of the brain.